The Efficiency and Equity of the Tax and Transfer System in France - Balazs Egert (Center for Economic Studies and ifo Institute (CESifo), 2013)
Taxes and cash transfers reduce income inequality more in France than elsewhere in the OECD, because of the large size of the flows involved. But the system is complex overall. Its effectiveness could be enhanced in many ways, for example so as to achieve the same amount of redistribution at lower cost. The French tax code should be simplified and changed less frequently. High statutory rates are coupled with a wide range of effective tax rates resulting from a multitude of tax expenditures. There is a need for base broadening combined with lower rates throughout the system, including VAT. The tax wedge on labour is high, except at the bottom of the wage distribution, which can reduce worker participation and job offers. Greater neutrality both across different capital asset classes but also within specific taxes, and shifting taxes from labour and capital inputs to environmental and property taxes would improve economic outcomes. Likewise, the system of social and family benefits should be simplified to enhance transparency and consistency. Eliminating schemes that let people leave the labour market early, abolishing the pension privileges of specific occupational groups and internalising the costs of survivors' pension benefits would increase fairness while at the same time generating savings. Better labour-market performance would result from increasing job-search incentives and shortening the parental leave allowance.
Keywords: D30; H20; H30; H50; H55; H70; J20; J30; 330; taxation; cash transfers; income inequality; redistribution